1991
DOI: 10.1002/mrm.1910170124
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting 39K NMR detectability in rat tissue

Abstract: In this study we have found that NMR detectability of 39K in rat thigh muscle may be substantially higher (up to 100% of total tissue potassium) than values previously reported of around 40%. The signal was found to consist of two superimposed components, one broad and one narrow, of approximately equal area. Investigations involving improvements in spectral parameters such as signal-to-noise ratio and baseline roll, together with computer simulations of spectra, show that the quality of the spectra has a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…While the intracellular sodium has been found to be totally visible in perfused hearts (24, 28,38), and the extracellular sodium has been found to be totally visible in the extracellular space in cartilage ( 3 9 ) , the possibility that the NMR visibility changes with pathology in either the intracellular or extracellular spaces must always be kept in mind. The specific experimental conditions chosen are responsible for the NMR visibility (28,38,40).…”
Section: Discussionmentioning
confidence: 99%
“…While the intracellular sodium has been found to be totally visible in perfused hearts (24, 28,38), and the extracellular sodium has been found to be totally visible in the extracellular space in cartilage ( 3 9 ) , the possibility that the NMR visibility changes with pathology in either the intracellular or extracellular spaces must always be kept in mind. The specific experimental conditions chosen are responsible for the NMR visibility (28,38,40).…”
Section: Discussionmentioning
confidence: 99%
“…Technical developments to increase the utility of 23 Na continue [147,148]. In vivo studies using 39 K have been more limited, as they are even more challenging than 23 Na studies [149,150]. 23 Na and 39 K studies in cells and perfused organs may take advantage of the use of shift reagents, anionic chelated complexes of paramagnetic lanthanides such as dysprosium bis(tripolyphosphate) (Dy(PPPi) 2 7-), which shift the frequencies of the extracellular ions sufficiently away from the intracellular resonances to resolve the difference [151][152][153].…”
Section: Myoinositol: An Indicator Of Inflammation and A Putative Markementioning
confidence: 99%
“…Similarly, a TmDOTP shift reagent was used to assist 39 K NMR measurement of intracellular potassium during ischemia in the perfused guinea pig heart [234]. A number of studies have demonstrated the usefulness of 39 K NMR for in vivo measurement of potassium levels and its transport in a range of different rat tissues including blood, brain, muscle, kidney, liver, testes and mandibular salivary gland [235][236][237][238]. A number of feasibility studies have also been performed for 39 K-MRI analysis of human muscle ( Figure 17) and brain [239][240][241].…”
Section: F Ementioning
confidence: 99%